The Effect of Music Listening on Anxiety Levels in Post-Subarachnoid Block Anaesthesia Patients - Prandani, Muhammad Yogi; Kurniawaty, Juni; Apsari, Ratih Kumala Fajar (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Background: The patients’ perioperative conditions can affect post-operative anxiety. Subarachnoid block anaesthesia can increase the incidence of post-operative anxiety. Methods to reduce post-operative anxiety are divided into pharmacological, with the administration of sedative drugs, and non-pharmacological, with holistic education, acupuncture, listening to music during surgery, and othersObjective: This study aims to observe the effect of listening to music on the anxiety level of surgical patients undergoing subarachnoid block anesthesia.Methods: This study was a Randomized Controlled Trial (RCT), with an intervention group (n=50) listening to music after subarachnoid block during surgery and a control group (n=50) receiving standard routine anesthetic care. Anxiety assessment using the STAI score and vital signs were performed at 3 different times in both groups.Results: There were no differences in patient characteristics between the two groups. Anxiety measurement in the reception room (X1) showed 37 patients (74%) and 31 patients (62%) with moderate anxiety in the intervention and control groups, respectively (p>0.05). There was no difference in patient anxiety levels between the two groups (p>0.05) in the operating room (X2). Post-operative anxiety measurement in the recovery room (X3) showed 43 patients (86%) with low anxiety in the intervention group, compared to 32 patients (64%) in the control group. Patients who listened to music during surgery had a lower level of post-operative anxiety compared to the control group (p=0.011). Conclusion: Listening to music can reduce post-operative anxiety in patients undergoing surgery with subarachnoid block, compared to patients receiving standard routine care